THE FOLIAR ANATOMY AND MICROMORPHOLOGY OF ALOE FEROX MILL. (ASPHODELACEAE) - Wintola, Olubunmi Abosede; Afolayan, Anthony Jide (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: The genus Aloe has been the subject of several chemotaxonomic and phytochemical investigations. Aloe ferox is an important source of biologically active compounds like anthrones, chromones, pyrones, and flavonoids. It is a plant used extensively in traditional medicine. Despite the myriad of studies on the pharmacological profile of the plant, there still exists a dearth of scientific literature on the anatomical and morphological attributes of this important medicinal plant. Materials and methods: Hence, the objective of this study was to examine the foliar anatomy and micromorphological characteristics of A. ferox using light microscope and scanning electron microscope and to determine the elemental composition of the leaf sections by energy dispersive x-ray spectroscopy. Results: Epidermal cells varied from round, square to hexagonal, with distinctive anticlinal walls and sunken stomata, equally distributed on both the adaxial and abaxial surfaces were observed. There were vertically elongated palisade cells with numerous chloroplasts in the palisade mesophyll layer. The EDXS analysis revealed Ca, K, S, Al, Mg, and Si as the major constituents of crystals present in the mesophyll. Conclusion: Information on the foliar anatomy and micromorphology can further enlightened our perceptions on the inherent interrelationships between structure and function as regards the synthesis and secretion of bioactive secondary metabolites by plants.